Dampak Covid-19 terhadap Sektor Industri - Jodi Wahyudi; Desiyana (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this study is to find out what Rhenaldi Kasali's perception is in the change house's YouTube channel entitled "If there is a real recession, then do this". In this study, the researcher used a descriptive qualitative method using notes because the source of the material was identified by listening to oral narratives. The results of this study explain that the impact of COVID-19 has changed the global order in various aspects of life, including the industrial sector. In this journal, we conduct an in-depth analysis of the impact of the COVID-19 pandemic on industrial sectors around the world. We take a look at how key industrial sectors have been affected by the social distancing, reduced demand, and supply chain disruptions caused by this pandemic. We also analyze the steps taken by the government and companies in dealing with the challenges faced and their impact on the industrial sector.